FTIR Interaction between Glycine and DPPC in hydrated state - Ale, Norma Mercedes (2013)
This glycine`s family (betaine, carnitine, dimethylglycine or glycine) takes part in a variety of biochemical reactions. The main function of a protector is to regulate loss and exchange of water in the biological structures. The protective capacity of these compounds on the membranes has been studied on numerous occasions.The existing information is fundamentally empirical, and do not know the mechanisms of interaction of these compounds with the membrane at molecular level. The aim of this work is analyze the interaction of the main functional groups of dipalmitoylphosphatidyl choline (DPPC) with glycine (gly) by infrared spectroscopy Fourier Transform (FTIR) in hydrated state. Our results revealed intermolecular interactions between the headgroups of DPPC and gly. These interactions would indicate that the phosphate group of the lipid membrane forms hydrogen bonds with gly in replacement of structured water.